HUMAN RESOURCE MANAGEMENT PRACTICES AND ITS OUTCOMES IN INDIAN PUBLIC SECTOR BANKS - Mangaleswaran, T.; Srinivasan, P.T. (My University, 2011)
The purpose of this study is to find out the Human Resource Management Practices (HRMP) and its outcomes viz. job satisfaction and organizational commitment in Indian public sector banks. HRMP have been studied extensively among manufacturing, service and small medium enterprises. However, only a few studies have addressed the banking industry. Surprisingly, the research studies of this nature have rarely been conducted to assess HRMP and its outcomes in banking environment. Through the survey method by the use of a structured questionnaire designed to test employee’s perceptions, the data were collected. Three public sector banks in India extended cooperation for this study It was targeted to elicit 600 responses from the Indian Public Sector Banks’ employees- 200 from each of the banks. Confirmatory factor analysis, Cronbach alpha, Stepwise Multiple Regression and Structural equation model (Path analysis) were used for various analyses of this study. HRMP are significant predictors of Job Satisfaction and Organizational Commitment; Job Satisfaction dimensions also significantly predict Organizational Commitment; HRMP lead to Job Satisfaction and Organizational Commitment.